2010
DOI: 10.4028/www.scientific.net/ssp.160.287
|View full text |Cite
|
Sign up to set email alerts
|

The Exoskeleton of the American Lobster – From Texture to Anisotropic Properties

Abstract: The exoskeleton of the crustacean Homarus americanus, the American lobster, is a biological multiphase composite consisting of a crystalline organic matrix (chitin), crystalline biominerals (calcite), amorphous calcium carbonate and proteins. One special structural aspect is the occurrence of pronounced crystallographic orientations and resulting directional anisotropic mechanical properties. The crystallographic textures of chitin and calcite have been measured by wide-angle Bragg diffraction, calculating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…α-Chitin is the most abundant polymorph; it occurs in fungal and yeast cell walls, and in the arthropod cuticle in general: the biological composite materials forming the exoskeleton of the lobster Homarus americanus and the crab Cancer pagurus have shown that all parts of the exoskeleton were optimized to fulfill different functions according to different eco-physiological strains sustained by the animals [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The hard chitinous tissues found in some invertebrate marine organisms are paradigms for robust, lightweight materials.…”
Section: Introduction and Scopementioning
confidence: 99%
“…α-Chitin is the most abundant polymorph; it occurs in fungal and yeast cell walls, and in the arthropod cuticle in general: the biological composite materials forming the exoskeleton of the lobster Homarus americanus and the crab Cancer pagurus have shown that all parts of the exoskeleton were optimized to fulfill different functions according to different eco-physiological strains sustained by the animals [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The hard chitinous tissues found in some invertebrate marine organisms are paradigms for robust, lightweight materials.…”
Section: Introduction and Scopementioning
confidence: 99%
“…While other groups have reported that stereochemistry controlled calcite nucleation in both P. carterae and E. huxleyi [ 46 , 47 ]. In marine invertebrates e.g., lobsters, acidic polysaccharides with carboxyl and sulfate functional groups have been shown to orientate CaCO 3 nucleation [ 48 ]. In general, there is strong qualitative evidence in the literature that indicates the chemical structure of polysaccharides contributes to controlling biomineralisation processes [ 26 , 45 , 47 ].…”
Section: Coccolithophore Organicsmentioning
confidence: 99%